Community assistance in the utilization of palm coir fiber - Fathur Rahman Rustan; Muhammad Buttomi Masgode; Arman Hidayat; Haerul Purnama; Al Tafakur La Ode; Arya Dirgantara; Retno Puspaningtyas (Community Empowerment, 2022)
The community assistance program in utilizing oil palm coir in Kolaka Regency, Southeast Sulawesi for supporting materials from the GRC mixture is a new breakthrough in the use of palm coir waste. This activity is expected to overcome the problem of oil palm coir waste and make it a new economic source for the surrounding community. The purpose of this program is to increase public knowledge in utilizing palm oil coir waste so that it can be of economic value and to increase public understanding in the process of making GRC by utilizing palm coir waste. The method used is assistance in the utilization of palm coir fiber as an added material in the manufacture of GRC plates. The results of the monitoring and evaluation activities resulted in the response that the surrounding community could process palm oil coir waste into a commodity that has economic value and additional knowledge to utilize palm oil coir waste in the manufacture of Glassfiber Reinforced Cement (GRC) as part of innovation in the construction sector.